EFEKTIVITAS BULAN BAHASA BALI TAHUN 2020 DALAM UPAYA PELINDUNGAN BAHASA AKSARA DAN SASTRA BALI DI KABUPATEN KARANGASEM - I Wayan Jatiyasa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
The Balinese Language Month in Karangasem Regency is simultaneously held in February, referring to the Bali Governor Regulation No. 80 of 2018. The Balinese Language Month of 2020 is very effective in protecting the Balinese language, script and literature in Karangasem Regency. This activity was able to arouse the interest and potential of Karangasem Regency community in the field of Balinese language, script, literature and culture. This is shown by the enthusiasm of the community in participating in competitions, parades, festival and coaching.Keywords: Effectiveness, Balinese Language Month, and Karangasem Regency